The overactive bladder model anatomical and morphological correlates - Iatsyna, O. I. (Journal of Education, Health and Sport, 2018)
After the overactive bladder modelling one could see the urinary ways in vivo changes registration using MRI with MR-urography before and after the diuretic load. The morphological investigations results proved the overactive bladder properties using MRI-registration. The internal organs and urinary ways showed no changes during the early terms. 30 days after the overactive bladder model induction one could register the morphological changes resulted in the ureterohydronephrosis development. The overactive bladder model stability and its adequate type to clinical condition was proved on the basis of the performed functional and morphological studies together with pathological changes dynamics characteristic for ureterohydronephrosis were studied.